A dual-plasmon coupling-enhanced WO 3-x -Au and its preparation method and application
Through the enhanced WO3-x-Au catalyst with dual plasma coupling, the problem that existing photocatalysts cannot effectively utilize the full spectrum is solved, and the utilization of full spectrum sunlight and catalytic performance is improved, which is suitable for efficient catalysis in the field of green chemicals.
Patent Information
- Application Number
- CN202310006726.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-04
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-01-04
AI Technical Summary
The existing photocatalysts have too wide band gaps, which cannot effectively utilize visible and infrared light, resulting in waste of solar energy and their catalytic performance is not enough to meet the needs of green synthesis.
The WO3-x-Au catalyst enhanced by dual plasma coupling was used to prepare a composite material of WO3-x nanobeam and Au nanospheres by solvent thermal reaction and photo-assisted reduction method. The full spectrum absorption characteristics of WO3-x and Au are used to achieve full spectrum absorption, and the catalytic performance is improved through coupling effect.
The utilization of full spectrum sunlight has been achieved, the catalytic performance has been significantly improved, and the catalytic performance can be quickly converted into para-aminophenol. It has excellent light absorption characteristics and catalytic performance, and is suitable for the green chemical field.
Smart Images

Figure CN116212870B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of plasma photocatalysis and fine chemical green synthesis, and specifically relates to a double plasma coupling enhanced WO 3-x -Au and its preparation method and application. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] In recent years, the two major issues of energy crisis and environmental pollution have attracted widespread attention. The development and utilization of new clean energy to deal with current energy and environmental problems has important strategic and practical significance. As an abundant and easily available clean energy, solar energy has attracted close attention from all over the world among many new energy sources. Therefore, the effective utilization and conversion of solar energy is an important research direction of photocatalysis at present. In addition, in addition to the traditional photocatalytic hydrogen production, oxygen production and pollutant degradation, photocatalytic fine chemical green synthesis has become a research hotspot in recent years. Using light energy as a driving force for green chemical synthesis, especially using organic hazardous waste as raw materials to obtain industrial products with high added value, is an effective way to achieve sustainable development and green development. However, most of the traditional photocatalysts currently have the problem of too wide a band gap, which can only absorb ultraviolet light for catalytic reaction, and cannot use visible light and infrared light sources, resulting in a huge waste of solar energy. Therefore, based on traditional semiconductors, the development of new photocatalytic materials with wide spectral response is crucial for the green synthesis of photocatalytic fine chemicals.
[0004] Plasma materials have unique light absorption properties and have become a research hotspot in the field of photocatalysis. The light absorption characteristics of plasma materials come from their own localized surface plasmon resonance (LSPR) effect. This effect can be explained as the strong absorption or scattering of photon energy by metal particles when the frequency of the incident light matches the collective oscillation frequency of free electrons on the surface of metal nanoparticles. The resonance absorption peaks of metal plasma materials are generally located in the visible light and near-infrared light regions, which can effectively utilize solar energy for catalytic reactions. In addition, in addition to metal plasma materials, degenerate semiconductor plasma materials (such as defective tungsten oxide, WO3-x) have received increasing attention due to their light absorption characteristics in the infrared light region. It can be seen that metal plasma materials and semiconductor plasma materials have a complementary relationship in the utilization range of the solar energy spectrum. Therefore, constructing a metal-semiconductor dual plasma material system is an effective solution to improve the efficiency of solar energy utilization. In addition, the coupling effect and energy transfer process between the two are also of great significance in improving the activity of photocatalysis. Summary of the invention
[0005] In order to solve the shortcomings of the prior art, the purpose of the present invention is to provide a dual plasma coupling enhanced WO 3-x -Au and its preparation method and application. WO in the present invention 3-x -Au dual plasma catalyst can simultaneously utilize WO 3-x and Au's light absorption characteristics, thereby achieving wide-spectrum absorption of solar energy and effectively improving the utilization rate of sunlight; in addition, the coupling effect between the two can further enhance the catalytic performance of the material system and promote the reaction of hydrogenation of p-nitrophenol to generate p-aminophenol; at the same time, the present invention also uses single-particle spectroscopy technology to verify the WO 3-x The energy transfer process between Au and the catalyst. The catalyst has the advantages of environmentally friendly constituent elements, simple and adjustable preparation method, easy to obtain reaction conditions, low cost and easy industrialization, so the catalyst has good application value.
[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0007] In the first aspect, the present invention provides a dual plasma coupling enhanced WO 3-x -Au preparation method, comprising the following steps:
[0008] Tungsten salt is added to the alcohol solution and stirred until a uniform solution is obtained. The precursor solution is subjected to a solvothermal reaction to obtain WO 3-x Nanobeam powder;
[0009] The prepared WO 3-x The nanobeam powder was dispersed in the solution and treated with light. A certain amount of chloroauric acid aqueous solution was added to the system for light-assisted reduction to obtain dual plasma coupling-enhanced WO 3-x -Au.
[0010] In a second aspect, the present invention provides a dual plasma coupling enhanced WO 3-x -Au, WO enhanced by the above dual plasmon coupling 3-x -Au is obtained by the preparation method.
[0011] Thirdly, the above dual plasma coupling enhanced WO 3-x -Application of Au in photocatalytic hydrogenation of p-nitrophenol to p-aminophenol.
[0012] In a fourth aspect, a method for photocatalytically hydrogenating p-nitrophenol to generate p-aminophenol comprises the following steps:
[0013] The above dual plasma coupling enhanced WO 3-x-Au is dispersed in a p-nitrophenol solution, which is then evacuated with argon in a dark place, and a sodium borohydride solution is injected into the container with a syringe. A xenon lamp is then used for light irradiation reaction, and a magnetic stirrer is used for vigorous stirring during the process.
[0014] The beneficial effects achieved by one or more technical solutions of the present invention are as follows:
[0015] The dual plasma coupling enhanced WO prepared in the present invention 3-x -Au by WO 3-x Compared with the single plasma system (WO 3-x Nanobeams or individual Au nanospheres), the dual plasma system can fully utilize the solar spectrum, thereby achieving full-spectrum solar-driven green synthesis of fine chemicals. 3-x -Au system, WO 3-x There is a coupling effect between WO and Au, and the light absorption capacity and near-field enhancement effect are significantly enhanced compared with the single component, and the catalytic performance of the composite system has been greatly improved. 3-x The photogenerated electrons excited by light can be transferred to Au by direct electron injection and participate in the catalytic reaction. This process not only promotes the 3-x The rapid separation of photogenerated electrons can increase the hot carrier concentration in Au, thereby accelerating the hydrogenation catalytic reaction. The use of single-particle fluorescence spectroscopy technology further verified the occurrence of this process at the experimental level.
[0016] WO in the present invention 3-x -Au as a photocatalytic p-nitrophenol hydrogenation catalyst showed excellent catalytic performance far exceeding that of a single component catalyst, and was able to quickly convert p-nitrophenol into p-aminophenol in a short time. Moreover, the catalyst was able to catalyze the reaction under visible light-driven conditions, indicating that the WO prepared by the method of the present invention 3-x -Au has excellent light absorption characteristics and catalytic performance, and has broad practical application prospects in the field of green chemical industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0018] Figure 1 WO prepared in Comparative Example 1 3-x WO prepared in Example 1 3-x -Au and WO prepared in Comparative Example 3 3-x -XRD pattern of Au-O2;
[0019] Figure 2 WO prepared in Example 1 3-x -Au(a) and WO prepared in Comparative Example 3 3-x -SEM morphology of Au-O2 (b);
[0020] Figure 3 WO prepared in Example 1 3-x -Au(a) and WO prepared in Comparative Example 3 3-x -Transmission electron microscopy schematic diagram of Au-O2 (b);
[0021] Figure 4 WO prepared in Comparative Example 1 3-x WO prepared in Example 1 3-x -Au and WO prepared in Comparative Example 3 3-x -Diffuse reflectance absorption spectrum of Au-O2;
[0022] Figure 5 This is a schematic diagram of the reaction of p-nitrophenol hydrogenating to p-aminophenol under the conditions of light and catalyst;
[0023] Figure 6 WO prepared in Comparative Example 1 3-x , Au NPs prepared in Comparative Example 2, WO prepared in Example 1 3-x -Au and WO prepared in Comparative Example 3 3-x Schematic diagram of the performance of hydrogenation of p-nitrophenol to p-aminophenol using -Au-O2. Among them, a is a schematic diagram of the change of p-nitrophenol concentration over time when catalyzed by different catalysts, and b is a schematic diagram of WO prepared in Example 1 3-x -Au catalytic reaction during the UV-visible absorption spectrum of p-nitrophenol as a function of catalytic time, from top to bottom are 0min, 5min, 10min, 15min, c, d are WO prepared in Example 1 under different light sources 3-x -Schematic diagram of the concentration change of p-aminophenol during Au catalytic reaction;
[0024] Figure 7 WO prepared in Comparative Example 1 3-x , Au NPs prepared in Comparative Example 2 and WO prepared in Example 1 3-x -Au single particle fluorescence image and fluorescence spectrum. Among them, a is the fluorescence image of AuNPs, b is the fluorescence image of WO 3-x -Au fluorescence image, c, d are comparisons of the fluorescence intensity spectra of the three samples. DETAILED DESCRIPTION
[0025] As mentioned in the introduction, the existing traditional semiconductor photocatalysts have the problem of too wide band gap to utilize visible light and infrared light, which wastes most of the energy in the solar spectrum and is not conducive to the effective absorption and utilization of solar energy. Therefore, the addition of plasma materials can effectively improve this situation. In addition, the dual plasma material system can form complementary advantages and basically achieve full spectrum absorption of solar energy. The coupling effect between the two can further improve the catalytic performance of the material. Based on the above analysis, the present invention proposes a dual plasma coupling-enhanced WO with full spectrum response. 3-x -Au, with good light absorption characteristics and excellent catalytic performance, has good application prospects in the field of green chemical industry.
[0026] The first typical embodiment of the present invention is a dual plasma coupling enhanced WO 3-x -Au preparation method, comprising the following steps:
[0027] Tungsten salt is added to the alcohol solution and stirred until a uniform solution is obtained. The precursor solution is subjected to a solvothermal reaction to obtain WO 3-x Nanobeam powder;
[0028] The prepared WO 3-x The nanobeam powder was dispersed in the solution and treated with light. A certain amount of chloroauric acid aqueous solution was added to the system for light-assisted reduction to obtain dual plasma coupling-enhanced WO 3-x -Au.
[0029] In one or more examples of this implementation, the tungsten salt is tungsten hexachloride, the alcohol is ethanol, and the concentration of the tungsten salt is 10-15 g / L.
[0030] In one or more examples of this embodiment, the temperature of the solvent thermal reaction is 160-230° C. and the time is 18-24 hours.
[0031] In one or more examples of this embodiment, the temperature of the light-assisted reduction is 5-25° C. and the time is 0.8-1.2 h.
[0032] In one or more examples of this embodiment, the concentration of the chloroauric acid aqueous solution is 0.05-0.2 M, and the volume is 0.5-1 mL.
[0033] In one or more examples of this implementation, the distance from the light source to the solution surface during the light-assisted reduction process is 10-25 cm.
[0034] A second typical embodiment of the present invention is a dual plasma coupling enhanced WO 3-x -Au, WO enhanced by the above dual plasmon coupling 3-x-Au is obtained by the preparation method.
[0035] In a third typical embodiment of the present invention, the dual plasma coupling enhanced WO 3-x -Application of Au in photocatalytic hydrogenation of p-nitrophenol to p-aminophenol.
[0036] A fourth typical embodiment of the present invention is a method for photocatalytically hydrogenating p-nitrophenol to produce p-aminophenol, comprising the following steps:
[0037] The above dual plasma coupling enhanced WO 3-x -Au is dispersed in a p-nitrophenol solution, which is then evacuated with argon in a dark place, and a sodium borohydride solution is injected into the container with a syringe. A xenon lamp is then used for light irradiation reaction, and a magnetic stirrer is used for vigorous stirring during the process.
[0038] In one or more embodiments of this embodiment, the dual plasma coupling enhanced WO 3-x -Au dosage is 5-15mg;
[0039] The concentration of p-nitrophenol solution is 0.1-0.3 mM and the volume is 20-40 mL;
[0040] Exhaust treatment time is 30-60min;
[0041] The concentration of sodium borohydride solution is 0.05-0.1M and the volume is 2-5mL;
[0042] The temperature of the photoreaction was kept constant at 15°C.
[0043] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.
[0044] Example 1
[0045] 0.96g of tungsten hexachloride was added to 80ml of ethanol, and the solution was sealed and stirred at 25 degrees until the solid was completely dissolved to form a uniform precursor solution. The precursor solution was transferred to a 100ml polytetrafluoroethylene reactor, which was completely sealed and placed in an electric heating box for solvent thermal reaction at 220 degrees for 20 hours. After the reaction was completed, it was cooled naturally and centrifuged and washed to obtain WO 3-x Nanobeam.
[0046] Take 0.1g of WO 3-xThe nanobeam powder was placed in a reactor, and 100 ml of deionized water was added for ultrasonic dispersion for 20 min. Subsequently, the uniformly ultrasonically dispersed suspension was irradiated with full light using a xenon lamp, and 1 ml of 0.05 M chloroauric acid aqueous solution was gradually added. During this process, a magnetic stirrer was used for vigorous stirring, and the irradiation time was 40 min. After the end, the suspension was centrifuged, washed, and dried to obtain dual plasma coupling enhanced WO 3-x -Au, denoted as WO 3-x -Au.
[0047] Example 2
[0048] 1.2g of tungsten hexachloride was added to 80ml of ethanol, and the solution was sealed and stirred at 25 degrees until the solid was completely dissolved to form a uniform precursor solution. The precursor solution was transferred to a 100ml polytetrafluoroethylene reactor, which was completely sealed and placed in an electric heating box for solvent thermal reaction at 180 degrees for 24 hours. After the reaction was completed, it was cooled naturally and centrifuged and washed to obtain WO 3-x Nanobeam.
[0049] Take 0.1g of WO 3-x The nanobeam powder was placed in a reactor, and 100 ml of deionized water was added for ultrasonic dispersion for 20 min. Subsequently, the uniformly ultrasonically dispersed suspension was irradiated with full light using a xenon lamp, and 0.5 ml of a 0.05 M aqueous solution of chloroauric acid was gradually added. During this process, a magnetic stirrer was used for vigorous stirring, and the illumination time was 40 min. After the end, the suspension was centrifuged, washed, and dried to obtain the dual plasma coupling enhanced WO 3-x -Au.
[0050] Example 3
[0051] 0.8g of tungsten hexachloride was added to 80ml of ethanol, and the solution was sealed and stirred at 25 degrees until the solid was completely dissolved to form a uniform precursor solution. The precursor solution was transferred to a 100ml polytetrafluoroethylene reactor, which was completely sealed and placed in an electric heating box for solvent thermal reaction at 230 degrees for 18 hours. After the reaction was completed, it was cooled naturally and centrifuged and washed to obtain WO 3-x Nanobeam.
[0052] Take 0.1g of WO 3-xThe nanobeam powder was placed in a reactor, and 100 ml of deionized water was added for ultrasonic dispersion for 20 min. Subsequently, the uniformly ultrasonically dispersed suspension was irradiated with full light using a xenon lamp, and 1 ml of 0.05 M chloroauric acid aqueous solution was gradually added. During this process, a magnetic stirrer was used for vigorous stirring, and the irradiation time was 40 min. After the end, the suspension was centrifuged, washed, and dried to obtain dual plasma coupling enhanced WO 3-x -Au.
[0053] Comparative Example 1
[0054] 0.96g of tungsten hexachloride was added to 80ml of ethanol, and the solution was sealed and stirred at 25 degrees until the solid was completely dissolved to form a uniform precursor solution. The precursor solution was transferred to a 100ml polytetrafluoroethylene reactor, which was completely sealed and placed in an electric heating box for solvent thermal reaction at 220 degrees for 20 hours. After the reaction was completed, it was cooled naturally and centrifuged and washed to obtain WO 3-x Nanobeam, denoted as WO 3-x .
[0055] Comparative Example 2
[0056] 2 ml of 1% chloroauric acid aqueous solution was added to 98 ml of deionized water and stirred for 30 min to obtain a uniform solution. The above solution was transferred to a flask and heated to boil using a sand bath apparatus, and the heating temperature of the process was 50 degrees Celsius. Subsequently, 1.2 ml of 1% trisodium citrate aqueous solution was added to the boiling solution and stirred vigorously for 30 min before stopping heating. After cooling naturally, Au nanoparticles were prepared, which were recorded as Au NPs.
[0057] Comparative Example 3
[0058] Take 50 mg of WO in Example 1 3-x -Au powder was placed in an agate mortar, 10 ml of anhydrous ethanol was added and the powder was repeatedly ground for 30 min, and then the sample in the mortar was transferred to a corundum crucible.
[0059] The crucible was oxygen annealed in a tube furnace. The annealing temperature was 400 degrees and the time was 1 hour. The tube furnace was vented with high-purity oxygen for 1 hour before the temperature was raised, and then annealed for 3 hours. After the annealing was completed, WO 3-x -Au-O2.
[0060] WO prepared in Comparative Example 1 3-x Nanobeams and WO prepared in Example 1 3-x -X-ray diffraction pattern (XRD) of Au is as follows Figure 1 a. Light-assisted synthesis of WO 3-x-Au can find obvious diffraction peaks of Au in the XRD diffraction pattern, indicating that this method can effectively load Au nanoparticles on WO 3-x Nanobeam; WO of Comparative Example 3 3-x -Au-O2 and WO of Comparative Example 1 3-x XRD comparison of nanobeams Figure 1 As shown in b, WO 3-x -Au-O2 also has obvious diffraction peaks of Au. Figure 1 a diffraction pattern comparison, WO 3-x -Au-O2 and WO 3-x -The XRD diffraction pattern of Au remained consistent and no crystal form change occurred.
[0061] WO prepared in Example 1 3-x -Au and WO prepared in Comparative Example 3 3-x -Au-O2 scanning electron microscope image (SEM) Figure 2 As shown. By comparison, it is found that the WO obtained by annealing in oxygen 3-x -The microstructure of Au-O2 has not changed compared with WO before annealing. 3-x -Au remains consistent, thus eliminating the influence of changes in micromorphology on catalytic activity.
[0062] WO prepared in Comparative Example 1 3-x Nanobeams and WO prepared in Example 1 3-x -Au samples showed that the gold nanoparticles were mainly loaded on WO 3-x The two ends of the nanobeam are loaded with WO 3-x The nanobeam morphology was well maintained and not destroyed.
[0063] WO prepared in Comparative Example 1 3-x Nanobeams and WO prepared in Example 1 3-x -Au and WO prepared in Comparative Example 3 3-x -The UV-visible diffuse reflectance spectrum (DRS) of Au-O2 samples is as follows Figure 4 As shown, by comparison, it can be seen that among the three samples, WO 3-x -Au has the best light absorption. WO obtained after annealing 3-x -The light absorption of Au-O2 in the near-infrared region is significantly weakened. This is because annealing in oxygen causes the oxygen vacancy concentration of the sample to decrease, which affects the plasma resonance absorption of the sample in the near-infrared region.
[0064] Example 4
[0065] Photocatalytic hydrogenation of p-nitrophenol (4-NP) to generate p-aminophenol (4-AP) activity test:
[0066] 1. Test method:
[0067] The photocatalytic hydrogenation reaction was carried out in a quartz reaction container. 10 mg of the catalyst obtained in Example 1 and Comparative Examples 1-3 were respectively dispersed into 30 ml of a 0.2 mM p-nitrophenol solution, and then argon gas was exhausted in the dark for 30 min. Then, 3 ml of a 0.05 M sodium borohydride solution was injected into the container with a syringe, and then a xenon lamp was used to illuminate the reaction, and a magnetic stirrer was used for vigorous stirring during the process. The reaction temperature was controlled at room temperature 15 degrees.
[0068] 2. Test results:
[0069] The schematic diagram of the reaction process of p-nitrophenol generating p-aminophenol under the action of light and catalyst is shown in Figure 5 shown.
[0070] WO prepared in Comparative Example 1 3-x Nanobeams, Au NPs prepared in Comparative Example 2, WO prepared in Example 1 3-x -Au and WO prepared in Example 2 3-x -Au-O2 sample catalytic activity for p-nitrophenol hydrogenation Figure 6 As shown in a, it can be seen that among all samples, AuNPs have a certain catalytic activity, WO 3-x -Au has the best catalytic activity, WO 3-x The catalytic activity of the nanobeams is basically negligible, which indicates that Au is the main active site in the catalytic reaction, and WO 3-x There is a certain synergistic effect between WO and Au, which improves the catalytic performance of the composite. 3-x -The catalytic activity of Au-O2 is compared with that of WO 3-x -Au was significantly suppressed because the annealing process in oxygen reduced the oxygen vacancy concentration of the sample, which made the overall plasma resonance light absorption of the sample and WO 3-x The synergistic effect between Au and the sample was weakened, resulting in a decrease in the catalytic activity of the sample.
[0071] Figure 6 b is sample WO 3-x -Au catalyzed hydrogenation of p-nitrophenol. As can be seen from the figure, the light absorption of the solution at 400nm gradually decreases with time, while the light absorption near 300nm gradually increases, which indicates that p-nitrophenol in the solution gradually generates p-aminophenol under the catalytic action.
[0072] In order to further illustrate the synergistic effect in the photocatalytic process, the WO prepared in Example 1 3-x -The catalytic activity of Au under different light sources Figure 6 c and Figure 6 d. The figure shows that under the conditions of ultraviolet light, visible infrared light and full light irradiation, the catalytic activity of full light irradiation is the best, and the catalytic activity of full light irradiation is significantly higher than the sum of the catalytic activities of ultraviolet light and visible infrared light. This is because during the full light irradiation process, ultraviolet light can convert WO 3-x The electrons in the valence band are excited to the conduction band, which further promotes the plasma resonance absorption in the system.
[0073] Based on the above test results, it is speculated that in WO 3-x -Au, exists from WO 3-x The energy transfer from Au to Au is the main active site of the catalytic reaction. The energy transfer between the two forms a synergistic effect, thereby improving the catalytic ability of the material system. 3-x -Au single particle fluorescence image and luminescence spectrum Figure 7 As shown in Figure b, Au nanoparticles and WO 3-x The fluorescence emission of the nanobeams is very weak. However, the WO 3-x -Au has a very significant fluorescence emission peak near 550nm, which can be attributed to the fluorescence emission of Au. Therefore, we can draw a conclusion: WO 3-x After being combined with Au, the fluorescence emission of Au was significantly improved, which fully demonstrated that there was a 3-x The energy transfer from Mg to Au plays an important role in improving the catalytic activity.
[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for photocatalytic hydrogenation of p-nitrophenol to produce p-aminophenol, characterized in that: The following steps are involved: The dual plasmon coupling enhanced WO 3-x -Au is dispersed into a p-nitrophenol solution, which is then evacuated with argon in a dark place, and a sodium borohydride solution is injected into the container with a syringe, and then a xenon lamp is used for light reaction, and a magnetic stirrer is used for vigorous stirring during the process; The dual plasma coupling enhanced WO 3-x -Au preparation method includes: 0.96 g of tungsten hexachloride was added to 80 mL of ethanol, and the solution was sealed and stirred at 25 °C until the solid was completely dissolved to form a uniform precursor solution. The precursor solution was transferred to a polytetrafluoroethylene reactor with a volume of 100 mL, and after being completely sealed, it was placed in an electric heating box for solvent thermal reaction at 220 °C for 20 hours. After the reaction was completed, it was naturally cooled and centrifuged and washed to obtain WO 3-x Nanobeams; Take 0.1g of WO 3-x The nanobeam powder was placed in a reactor, and 100 mL of deionized water was added for ultrasonic dispersion for 20 min. Subsequently, the uniformly ultrasonically dispersed suspension was irradiated with full light using a xenon lamp, and 1 mL of 0.05 M chloroauric acid aqueous solution was gradually added dropwise. During this process, a magnetic stirrer was used for vigorous stirring, and the irradiation time was 40 min. After the end, the suspension was centrifuged, washed, and dried to obtain dual plasma coupling enhanced WO 3-x -Au, denoted as WO 3-x -Au; Gold nanoparticles are mainly loaded on WO 3-x The two ends of the nanobeam are loaded with WO 3-x The nanobeam morphology was well maintained and not destroyed.
2. The method for photocatalytic hydrogenation of p-nitrophenol to produce p-aminophenol as claimed in claim 1, characterized in that: Dual plasmon coupling enhanced WO 3-x -Au dosage is 5-15mg; The concentration of p-nitrophenol solution is 0.1-0.3 mM and the volume is 20-40 mL; Exhaust treatment time is 30-60min; The concentration of sodium borohydride solution is 0.05-0.1M and the volume is 2-5mL; The temperature of the photoreaction was kept constant at 15°C.
Citation Information
Patent Citations
Supported two-dimensional layered molybdenum sulfide composite material and preparation method and application thereof
CN105664976A